Humor and grammar in the foreign language classroom. Can we laugh at anything? - Fernández, Silvia Gabriela; Araya , Teresa (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
This article describes a set of classroom activities designed for EFL university students of the Teacher and Translator Training Courses to integrate into the EFL classroom a scientific approach to grammar teaching and a decolonial perspective to foreign language teaching. Firstly, the reasons why humor has been chosen as a means to introduce both a grammatical teaching point such as structural ambiguity and tackle hegemonic social and racial stereotypes are accounted for. This is followed by a description of the learning context and a description of the activities proper. The conclusion captures the challenges of adopting both enquiry-based learning and a decolonial approach to EFL teaching in a university setting.